Pengaruh Lingkungan Budaya terhadap Bisnis Internasional - Junita Pratiwi; Hendra Hendra (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find out how culture influences international business. Research carried out uses literature (libraries), in the form of books, notes, or reports of research results from previous research. The data collection technique in this research is by reviewing research journals or scientific articles, books, documents, or other information related to the research title. After the data is collected, data analysis is then carried out. Data analysis in this research is analyzing and synthesizing these documents to be studied and become new ideas to support research results. The results of this research are that culture is a collection of values, beliefs, behavior, habits and attitudes that differentiate one society from others. The culture of a society determines the rules that govern how companies are run in that society. Cultural factors are one aspect that has a very big influence on international marketing activities. Culture is one of the main foundations that is used as a basis for business people to carry out their business activities. This is because culture at the international level is very diverse, different and dynamic, so it requires different methods, strategies and approaches to market these products.